Arrhythmogenic pattern of rheumatic fever - Nashwa Mabrouk Abdelkareem Gad; Maha Korani Mohammad; Mohammad Ali Hegazi; Mohammad Hesham Safouh (Cairo : Nashwa Mabrouk Abdelkareem Gad, 2010)
Rheumatic fever and rheumatic hart disease are still highly prevalent in many parts of the world including Egypt . In different studies , RF was associated with different types of arrhythmias either with or without evidence of underlying carditis by indefinite mechanism . So this study aimed to detect and to delineate the arrhythmogenic pattern of rheumatic fever (acule and chronic and after treatment) through arrhythmia screen among ninety - six patient suffering from rheumatic fever compared to fifty healthy children
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Arrhythmia; Rheumatic fever; Rheumatic heart disease